Studi Tentang Daya Dukung Sumber Daya Manusia dalam Mengimplementasikan Permendagri No. 17 Tahun 2007: Studi pada Sekretariat Daerah Kabupaten Pangandaran - Hengky Paice Hermansyah; Nana Darna (International Forum of Researchers and Lecturers, 2024)
The problems in this study are regarding the carrying capacity of human resources at the Regional Secretariat of Pangandaran Regency, the management of Regional Assets at the Regional Secretariat of Pangandaran Regency, the factors that hinder the carrying capacity of human resources in implementing Permendagri No. 17 of 2007 at the Regional Secretariat of Pangandaran Regency and the efforts made to improve the carrying capacity of human resources in implementing Permendagri No. 17 of 2007 at the Regional Secretariat of Pangandaran Regency. The purpose of this study is to determine the carrying capacity of human resources at the Regional Secretariat of Pangandaran Regency, to determine the management of Regional Assets at the Regional Secretariat of Pangandaran Regency, to determine what factors hinder the carrying capacity of human resources in implementing Permendagri No. 17 of 2007 at the Regional Secretariat of Pangandaran Regency and to determine what efforts are made to improve the carrying capacity of human resources in implementing Permendagri No. 17 of 2007 at the Regional Secretariat of Pangandaran Regency. The research method used in this study is a qualitative research method because it is a study that can be used to reveal problems in the work life of government organizations so that it can be used as a policy to be implemented in order to achieve the goals that have been set. The results of the study obtained are mainly the limitations of human resource support, both quantity and quality, which causes the management of Regional Property at the Regional Secretariat of Pangandaran Regency to be less than optimal and at the same time becomes an inhibiting factor in implementing Permendagri No. 17 of 2007 so that efforts are needed as a solution for future improvements.